The Effect Of Lighting Design And Application On Limar Textile In Terengganu State Museum - Saeid Ali, Alaa Abdalla (2022)
The lighting application of a textile museum combines art, science, and engineering, whereby the lighting integrates the aesthetic value and the exhibition preservation requirements. Lighting can evoke sensations and emotions. It controls the perception of specific exhibitions, such as textiles. The quality of the lighting in the galleries is not determined solely by the source of the lighting, but also by the characters and the space configuration. The means by which the lighting hits the object and the architecture results in light penetration and reflected light, as well as how such lighting is accepted by the minds and eyes of the viewers. This research focuses on the lighting application of the limar textile exhibition gallery. This research emphasizes the lighting application in the Terengganu State Museum to help maintain better conservation of limar textiles by investigating the adverse effects of the lighting design. The selection of limar textile, by reason, is the essential cultural value that limar has in representing the history and culture of Malaysia. Therefore, this delicate and worthy textile needs to be conserved to preserve it for the upcoming generation.